Thrombectomy vs. Systemic Thrombolysis in Acute Embolic Stroke with High Clot Burden: A Retrospective Analysis - Meyne, J. K.; Zimmermann, P. R.; Rohr, A.; Riedel, C.; Hansen, H. C.; Pulkowski, U.; Thie, A.; Holst, T.; Papengut, F.; Stingele, R.; Schepelmann, K.; Jansen, O.; Deuschl, G.; Binder, A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: The efficacy of i. v. thrombolysis in acute stroke with high clot burden is limited. Successful recanalization is very unlikely if the thrombus length exceeds 7 mm. Thus this retrospective controlled study evaluated the efficacy and safety of neurothrombectomy in the treatment of acute embolic stroke in patients selected by a thrombus length of ≥ 8 mm using the stent retriever Trevo® device.Materials and Methods: 40 patients with acute occlusion of the anterior intracranial arteries with a thrombus length of ≥ 8 mm were treated with neurothrombectomy. We compared the outcome with a historical cohort of 42 patients with a thrombus length of ≥ 8 mm that received i. v. thrombolysis only. Clinical outcome was assessed by modified Rankin scale in both groups at discharge and on day 90.Results: Patients did not differ in age, mRS on admission, thrombus length or time from symptom onset to i. v. thrombolysis, but the thrombectomy group had higher NIHSS on admission. Successful recanalization was achieved in 33/40 patients (83 %) with neurothrombectomy. 15 patients received i. v. thrombolysis prior to neurothrombectomy. Median mRS at discharge was 3.5 (1.25 – 5) vs. 5 (4 – 6; p < 0.01) and on day 90 3 (1 – 4) vs. 5 (4 – 6; p < 0.01). Symptomatic hemorrhage occurred in 3 vs. 7 patients. 3 vs. 17 patients died within 90 days (thrombectomy vs. control each). There were only a few intervention-related complications.Conclusion: Thrombectomy in acute stroke with high clot burden using the Trevo® device has a low risk and improved clinical outcome compared to i. v. thrombolysis alone. Treatment selection by a clot length of ≥ 8 mm might be a powerful approach to improve the outcome of mechanical thrombectomy.Key Points:• Clot length of ≥ 8 mm might be a valuable criterion for indicating neurothrombectomy.• Thrombolysis only in high clot burden is associated with poor clinical outcome.• Thrombectomy using the Trevo® stent retriever is safe and effective.Citation Format:• Meyne JK, Zimmermann PR, Rohr A. et al. Thrombectomy vs. Systemic Thrombolysis in Acute Embolic Stroke with High Clot Burden: A Retrospective Analysis. Fortschr Röntgenstr 2015; 187: 555 – 560
Keywords: stroke; thrombectomy; thrombolysis; stent retriever